Redox-coupling with RPTPɣ regulates the growth factor response of EGFR - Joshi, Maitreyi S. (Technische Universität Dortmund, 2021)
Somatic cells rely on surface receptors like receptor tyrosine kinases (RTK) that are situated at the cell-surrounding interface to sense the environmental cues encoding the information about nutrients, cell growth and tissue damage. Proto-oncogenic epidermal growth factor receptor (EGFR) is a prominent RTK that binds to extracellular epidermal growth factor (EGF) and transduces the associated signal patterns inside the cell. Spatial re-organization of EGFR and its interactions with protein tyrosine phosphatases (PTPs) bridge EGF-binding to EGFR signaling to yield diverse cell fate outcomes. By exerting their phosphatase activities PTPs regulate the sensitivity and response dynamics of EGFR to growth factors. This raises a question on how do PTPs inhibit the spurious activation of EGFR without hindering its ligand dependent activation. In this thesis, the coupling of EGFR with plasma membrane (PM)-based receptor-like protein tyrosine phosphatase-ɣ(RPTPɣ) and endoplasmic reticulum (ER)-bound T-cell protein tyrosine phosphatase (TCPTP) is examined to decipher the regulatory mechanisms that make EGFR capable of responding to the growth factor signals. We prove that expression of RPTPy is essential to suppress the anomalous activation of EGFR. The lack of RPTPɣ associated phosphatase activity makes the system susceptible to ligand-independent activation that turns it blind to the upcoming EGF signals. Consequently, cancer cells lacking RPTPɣ expression exhibit constitutive activity of EGFR. On the other hand, inhibition of RPTPɣ activity is necessary to trigger the activation of EGFR. This is achieved by EGF induced oxidation of the catalytic cysteine of RPTPɣ by the activation of reactive oxygen species (ROS) generating NOX-complexes. In the absence of NOX-activity, activation of EGFR is inhibited as a consequence of unhindered RPTPɣ catalytic activity. The regulation of EGFR response by the phosphatase activity of RPTPɣ and the EGFR kinase activity dependent regulation of RPTPɣ generates a ROS actuated toggle switch at the PM. By designing a live-cell imaging probe for the spatial resolution of oxidized proteins, we show that the EGFR activity dependent oxidation of RPTPɣ happens at the PM by localized ROS production. Vesicular recycling reduces RPTPɣ and restores its catalytic activity by exposing it to the reducing environment of the cytoplasm. Additionally, endocytosis of EGFR establishes its interaction with TCPTP that regulates EGFR signaling duration by dephosphorylation. Therefore, vesicular recycling couples the redox cycle of RPTPɣ to the activity cycle of EGFR and also maintains the reversibility in the system. The interaction between RPTPɣ and monomeric EGFR spanning from the plasma membrane to recycling endosomes adds a spatial dimension to their regulation. By demonstrating its coupling with EGF-induced EGFR activity, we prove redox regulation of RPTPy as a major coordination mechanism that prevents EGFR from attaining uncontrolled signaling but allows for its EGF dependent signal propagation.
Keywords: Epidermal growth factor receptor; Protein tyrosine phosphatase; Growth factor response; Reactive oxygen species; Toggle-switch dynamics; Signaling network; 570; 540; Phosphatasen; Kinasen